Bentuk dan Dampak Reviktimisasi pada Remaja Korban Kekerasan Seksual - Manafe, Rizky Pradita; Benu, Juliana Marlin Y (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
This study explores the forms of revictimization experiences of sexual violence survivors who decided to report their cases through legal process and examines the impact on their mental health. The study utilized a multi-method design involving interviews and DASS-42. Qualitative data were analyzed thematic analysis, while quantitative data were presented using descriptive statistics. The study involved 10 female participants aged 13 to 17 years. Findings reveal several forms of revictimization, including power dynamics between perpetrator and victim, negative family reactions, and verbal abuse from the environment. Revictimization led to self-blame, self-isolation and intrusive sexual thought, and supported by quantitative data indicating high levels of anxiety (90%), depression (70%), and stress (40%) among participants. Consequently, there is a critical need for awareness among families and neighborhoods. Psychological support should be provided from the time of disclosure to the legal process in order to facilitate recovery and minimize further harm.